Chapter 1 Introduction - van Melik, Rianne (Taylor & Francis, 2023)
This chapter sets the ground for the argument and aim of this edited volume on marketplaces. The book investigates marketplaces as important urban spaces not as pre-given, fixed locations with clear demarcations in space and time but instead as dynamic and open entities with constant flows of people, goods and ideas. By applying a mobility perspective and focusing on movements, representations and practices, the contributions show how markets are literally intersections of many different kinds. Movement is about the mobile character of marketplaces, notably street markets and street vending. As ambulant places, many markets move from one place to another. They are temporary spaces of encounters of traders and their customers through which goods and ideas are exchanged. Representations touch upon dominant narratives about the meaning and value of markets. While in some cases, markets are perceived as 'relics of the past', there are also dominant discourses that claim that markets still have important socio-economic values in providing, among others, income, access to fresh food, conviviality and care. Practices are about activities performed at marketplaces and how these are regulated, experienced and embodied by traders, customers, planners and designers. Together, these three themes enhance our relational understanding of marketplaces as dynamic, networked and multi-layered spaces.